PMO-226 Differing phenotype in elderly IBD; should Montreal include an A4 category. (28th May 2012) - McNicol, A A; Kennedy, N; Satsangi, J; Arnott, I D
Abstract : Introduction: The phenotype of elderly-onset IBD is poorly described and knowledge lags behind that of other age-groups. While not the dominant age-group in the disease population, those diagnosed over 60 will compose a larger proportion it as the general population ages over the next decade. The Montreal classification for IBD stratifies related to age into three categories, 40(A3) the study aims to ascertain if disease phenotype varies between those aged 40–59 and those >60 with possibility of an A4 group becoming viable if variance is noted. Methods: 1957 patients with IBD were identified using the IBD database at the Western General Hospital. We selected all those UC (n=306) and CD (n=135) diagnosed at age 40 and over (A3) and subdivided the group in to those over and under 60. The diagnosis adhered to the criteria of Lennard-Jones and IBD was categorised according to the Montréal classification. Data collected included diagnosis, age at diagnosis, disease distribution, disease behaviour and smoking history. Follow-up were available for 5 years following diagnosis. Analysis of the groups was undertaken using χ 2 and Fishers exact test. Results: Gender of CD patients in the different age groups (40–59; M/F=53/96. >60; M/F=10/49 p=0.0115) illustrated a higher proportion of women in the >60 group. CD patients who were diagnosed over the age of 60 had more isolated colonic disease at diagnosis. (L2; 40–59 N=28/77, >60 N=37/58, p=0.0032 L3; 40–59 N=15/77, >60 N=2/58 p=0.0073). By 5 years of follow-up these differences were no longer significant. There was do difference in disease behaviour or smoking history. UC patients had more left sided disease and less distal disease at diagnosis (E1; 40–59 N=70/204, >60 N=20/102, p=0.0079 E2; 40–59 N=88/204, >60 N=57/102 p=0.039). Smoking history showed a greater proportion of former smokers in the >60 group (40–59 N=108/216, >60 N=70/107 p=0.0058). Conclusion: Disease phenotype at Dx in both UC and Crohn's differs in the over-60s at diagnosis but normalises to that of the A3 population at follow-up. This data suggests that the introduction of an additional Montreal age classification, A4, would be clinically meaningful. Further analysis will demonstrate whether response to treatment differs in this age group. Competing interests: None declared.